Counseling in Social Work Practices during the Covid-19 - meiti Subardhini (WELFARE : Jurnal Ilmu Kesejahteraan Sosial, 2021)
This study aims to describe the practice of counseling during the COVID-19 period, surveying several clients. This study was conducted using a qualitative method. With data collection techniques, namely interviews and documentation studies of several clients who had attended counseling during the COVID-19 pandemic. Some of the obstacles felt by the client, including: limited time, difficult to convey problems, not awake, network constraints, difficulty interpreting responses / difficult body language to read and so on. Likewise, counselors who provide services during the COVID-19 pandemic with distance counseling, there are several things that become obstacles, such as: obstacles in exploring problems due to limitations in interpreting the client's body language except through voice intonation, alternative choices of action / solutions are limited to technique. or short therapy / brief therapy etc. Therefore, the results of the researchers recommend that social workers in conducting long-distance counseling with the media pay attention to the following: 1) advantages and disadvantages in counseling services; 2) the use of technological assistance in the counseling service is courageous; 3) form of courageous counseling accuracy; 4) access to applications for courageous counseling services; 5) legal and regulatory aspects in the use of technology in counseling; 6) technical matters relating to technology in business and law if services are provided between regions or countries.Keywords: Remote Counseling, Social Work Practice, Covid-19